2017
DOI: 10.1007/s00221-017-5123-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous vagus nerve stimulation (tVNS) modulates flow experience

Abstract: of attention over exploitation of the current focus of attention, allowing rapid behavioral adaptation and resulting in decreased absorption scores. Furthermore, our findings corroborate the hypothesis that the vagus nerve and noradrenergic system are causally involved in flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 32 publications
(47 reference statements)
1
28
0
Order By: Relevance
“…TVNS, via activation of the LC-NE system, may facilitate all of these processes. Some studies already showed improvements in emotion recognition (Colzato et al, 2017 ) cognitive control (Sellaro et al, 2015 ; Steenbergen et al, 2015 ; Beste et al, 2016 ), adaptability (Fischer et al, 2018 ), flow experience (Colzato et al, 2018 ), declarative fear extinction (Burger et al, 2016 ), and associative memory (Jacobs et al, 2015 ) following transcutaneous vagus stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…TVNS, via activation of the LC-NE system, may facilitate all of these processes. Some studies already showed improvements in emotion recognition (Colzato et al, 2017 ) cognitive control (Sellaro et al, 2015 ; Steenbergen et al, 2015 ; Beste et al, 2016 ), adaptability (Fischer et al, 2018 ), flow experience (Colzato et al, 2018 ), declarative fear extinction (Burger et al, 2016 ), and associative memory (Jacobs et al, 2015 ) following transcutaneous vagus stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that tVNS affected posterror slowing (Sellaro et al, 2015), response selection functions (Steenbergen et al, 2015;Jongkees et al, 2018), response speed when two actions were executed in succession (Steenbergen et al, 2015), divergent thinking (Colzato et al, 2018a), and emotion recognition (Colzato et al, 2017;Sellaro et al, 2018). tVNS also significantly influenced inhibitory control processes (Beste et al, 2016) and decreased flow experience during a task (Colzato et al, 2018b). A study by Jacobs et al (2015) was the first study to investigate the effect of tVNS on memory performance.…”
Section: Introductionmentioning
confidence: 99%
“…Applying tVNS in order to stimulate LC activity has been shown to facilitate a wide range of affective and cognitive functions, including emotion recognition (Colzato, Sellaro, & Beste, 2017;Sellaro, de Gelder, Finisguerra, & Colzato, 2018), flow experience (Colzato, Wolters, & Peifer, 2018), divergent thinking (Colzato, Ritter, & Steenbergen, 2018), associative memory (Jacobs, Riphagen, Razat, Wiese, & Sack, 2015), attentional processing (Ventura-Bort et al, submitted), and various processes associated with cognitive control. For example, tVNS has been shown to increase post-error slowing (Sellaro et al, 2015) to speed responses in a stop-change paradigm without affecting the stopping response time (Steenbergen et al, 2015) and to reduce the commission of false alarms under challenging conditions in a response inhibition paradigm (Beste et al, 2016).…”
mentioning
confidence: 99%